Effect of Yoga on Dysmenorrhea in 6th Grade Elementary School Students at Rusunawa Health Center: A Quasi-Experimental Study - Nuryaningsih, Nuryaningsih; Rosyati, Heri (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: From 35 elementary school students in Marunda, 23 students (65.7%) had primary dysmenorrhea. Dysmenorrhea can interfere with student learning activities and concentration. Interventions need to be given so that students can increase their productivity and learning achievement. AIM: This study aims to analyze the effect of yoga on dysmenorrhea in 6th grade elementary school students at Rusunawa Health Center. MATERIALS AND METHODS: This study used a quasi-experimental approach with a non-equivalent control group design. The yoga group was given yoga practice for 3 months of the menstrual cycle. The sample consisted of 33 students in the yoga group and 33 students in the control group. Dysmenorrhea pain intensity was measured by Wong Baker Pain Rating Scale. Statistical tests used were Friedman test, Mann–Whitney test, and Ordinal Regression test. RESULTS: There was a significant difference in pain duration and pain intensity of dysmenorrhea in the past 3 months in the yoga group (p < 0.001). There was a significant difference in pain duration and pain intensity of dysmenorrhea between the yoga group and control group on the measurements in the 2nd month (p = 0.009; p < 0.001) and the 3rd month (p < 0.001; p < 0.001). CONCLUSIONS: Yoga had a significant effect in reducing the pain duration and pain intensity of dysmenorrhea in 6th grade elementary school students at Rusunawa Health Center. Midwives can educate elementary school students and young women in the working area of Rusunawa Health Center to use yoga as an alternative therapy to reduce dysmenorrhea.